2005
DOI: 10.1097/01.ede.0000147104.84424.24
|View full text |Cite
|
Sign up to set email alerts
|

Traffic Noise and Risk of Myocardial Infarction

Abstract: The results support the hypothesis that chronic exposure to high levels of traffic noise increases the risk for cardiovascular diseases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

13
241
2
8

Year Published

2005
2005
2017
2017

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 466 publications
(264 citation statements)
references
References 14 publications
13
241
2
8
Order By: Relevance
“…Our L eq and L max measures indicate exposure to very loud noise for periods somewhat comparable to the daily ranges associated with increased cardiovascular and psychosomatic health risks. 10,12,15,17,18,20,[33][34][35][36][37] However, we warn that these studies generally treated periodic exposures throughout the day, such as those due to proximity to rail systems or traffic. Most BART trips are likely to extend beyond one line segment; for round-trip commuters, such exposure will double in the course of a day.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our L eq and L max measures indicate exposure to very loud noise for periods somewhat comparable to the daily ranges associated with increased cardiovascular and psychosomatic health risks. 10,12,15,17,18,20,[33][34][35][36][37] However, we warn that these studies generally treated periodic exposures throughout the day, such as those due to proximity to rail systems or traffic. Most BART trips are likely to extend beyond one line segment; for round-trip commuters, such exposure will double in the course of a day.…”
Section: Discussionmentioning
confidence: 99%
“…10,17 Findings have also shown that children living amid chronic noise have elevated levels of stress-induced hormones as well as elevated blood pressure. 18,19 There is also evidence of negative behavioral outcomes of noise exposure as well, 10,20 including negative behavioral effects of noise on children's cognition, concentration and memory, 17,[19][20][21] and on school performance. 22 The level of noise on trains results from many interacting factors, 23 including wheel roundness (i.e., deviation from perfectly circular) and wheel trueness (side-toside wobble in shape), rail condition (e.g., "corrugation," banking, points, etc.…”
Section: Introductionmentioning
confidence: 99%
“…At the 56 locations successfully monitored for noise, 55 samples were successfully monitored for PM 2.5 and BC (one location's PM 2.5 measurement did not pass filter QA/QC checks after monitoring and the sample was removed from further analysis). All sites were monitored for NO 2 and NO.…”
Section: Air Quality and Noise Samplingmentioning
confidence: 99%
“…Epidemiologic studies, for example, suggest higher risks of cardiovascular disease, including myocardial infarction and hypertension among people exposed to higher levels of ambient noise, particularly traffic noise. [1][2][3][4][5] Ambient noise exposures have been linked to a variety of physical and mental responses, including effects on cardiovascular endpoints 6 and impairment of cognitive development in children. 7 Nighttime noise exposures may be especially harmful and have been associated with elevated blood pressure, 8,9 and a greater cardiovascular response when compared to daytime noise exposures.…”
Section: Introductionmentioning
confidence: 99%
“…The reported effects on sleep disturbance tend to be a reduction in the sleep period, arousals, awakenings, sleep stage modifications and autonomic responses (e.g. change in heart rate) (Vallet et al, 1983;Carter, 1996;Babisch et al, 2005). Moreover, the reduction in sleep quality has secondary impacts (generally felt the day after disturbance) including fatigue, low work capacity, reduced cognitive performance, changes in daytime behaviour as well as mood changes and associated negative emotions.…”
Section: Introductionmentioning
confidence: 99%